1988
DOI: 10.1111/j.1600-0749.1988.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and Scanning Electron Microscopy and Freeze‐Fracture Replication of Normal Human Melanocytes and Human Melanoma Cells in Tissue Culture

Abstract: Basic LM, TEM, SEM, and FFR appearances of a pure line of normal human melanocytes derived from foreskin, and a human melanoma line, in cell culture are described. Normal melanocyte cultures exhibit side by side, cells of widely different melanogenic activities--possible clones--and melanosomes of bizarre shape and internal structure are frequent. Aggregates of melanosomes, with or without associated amorphous material, and with no discernible limiting membrane are present within many cells, and occasional sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Based on ultrastructural study, the melanosomes of adult melanocytes were distributed singly along the dendrites, whereas they were aggregated in the perinuclear cytoplasm of neonatal melanocytes. It has been suggested that aggregates of melanosomes or macromelanosomes are manifestations of autophagic activity (Hirone and Eryu 1978;Nakagawa et al 1984;Ortonne and Perrot 1979) due to impaired evacuation of "constipated" melanosomes (Breathnach et al 1988). In nevus depigmentosus which appears to result from melanosome aggregation and a transfer block, melanocytes have poorly developed, stubby dendrites and aggregated melanosomes (Mosher et al 1993).…”
Section: Melanin Content and Distributionmentioning
confidence: 99%
“…Based on ultrastructural study, the melanosomes of adult melanocytes were distributed singly along the dendrites, whereas they were aggregated in the perinuclear cytoplasm of neonatal melanocytes. It has been suggested that aggregates of melanosomes or macromelanosomes are manifestations of autophagic activity (Hirone and Eryu 1978;Nakagawa et al 1984;Ortonne and Perrot 1979) due to impaired evacuation of "constipated" melanosomes (Breathnach et al 1988). In nevus depigmentosus which appears to result from melanosome aggregation and a transfer block, melanocytes have poorly developed, stubby dendrites and aggregated melanosomes (Mosher et al 1993).…”
Section: Melanin Content and Distributionmentioning
confidence: 99%